The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/aen.12198
|View full text |Cite
|
Sign up to set email alerts
|

The New World grass‐thrips genus Plesiothrips (Thysanoptera: Thripidae) and its palaeotropical relationships

Abstract: Morphological character states displayed by Plesiothrips Hood, a New World genus of grass-living thrips, are assessed. This assessment indicates that Plesiothrips shares more character states with genera from Southeast Asia, including the Trichromothrips genus-group, than with any New World Thripinae. Sorghothrips sakagami (Kudo) comb. n. is removed from Plesiothrips; Taeniothrips aberrans Crawford syn. n. is considered a new synonym of Plesiothrips amblycauda Hood; and an illustrated identification key is giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The collected specimens were preserved in collection fluid (nine parts 10% alcohol + one part glacial acetic acid + one ml Triton X-100 in 1000ml of the mixture). Specimens were balsam mounted for permanent preservation (Ananthakrishnan & Sen 1980) and they were subsequently sorted out and identified with the help of standard keys (Mound 1999;Mound et al 2016;Tong et al 2016). The images of all the three species were photographed with the help of a binocular research microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected specimens were preserved in collection fluid (nine parts 10% alcohol + one part glacial acetic acid + one ml Triton X-100 in 1000ml of the mixture). Specimens were balsam mounted for permanent preservation (Ananthakrishnan & Sen 1980) and they were subsequently sorted out and identified with the help of standard keys (Mound 1999;Mound et al 2016;Tong et al 2016). The images of all the three species were photographed with the help of a binocular research microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the anterior ocellus is situated anterior to frontal margin of compound eyes; and females have a highly reduced ovipositor, without reaching the apex of abdomen. Males have unusually small antennal segment III and greatly enlarged segments IV-VI with numerous long setae; tergite IX bears a pair of drepanae and sternites III and IV bear a pair of circular pore plates (Mound et al 2016).…”
mentioning
confidence: 99%
“…This table is based on Bondar 1931;Moulton 1932;Martinez 1975;Tsai et al 1992;Childers and Achor 1995;Mound and Marullo 1996;Lewis 1997;Fancelli 2004;Cavalleri and Mound 2012;Hoddle et al 2012;Lima and Milanez 2013;Thomazini and Lima 2014;Mound et al 2016;Lima and Miyasato 2017;Poorani and Thanigairaj 2019;Michael and Lima 2020;Lima 2021;ThripsWiki 2021. 5. Pronotum with six pairs of setae on posterior margin (Fig.…”
Section: Thrips Pusillus Bagnall Xmentioning
confidence: 99%
“…Many Thysanoptera groups are associated with forages. Most of them, such as Bregmatothrips Hood, 1912, Chirothrips Haliday, 1836and Plesiothrips Hood, 1915, are associated with Poaceae species (Mound 2011;Nakahara & Footit 2012;Mound et al 2016), and a few have been reported as occurring in or damaging legume pastures, such as Enneothrips enigmaticus Lima et al, 2022 (Thysanoptera: Thripidae) in Arachis pintoi Krapov & W.C. Gregory (Fazolin et al 2015;Lima et al 2022).…”
mentioning
confidence: 99%